2019
DOI: 10.1080/21691401.2019.1617729
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, identification and application of the novel metal-organic framework Fe 3 O 4 @PAA@ZIF-8 for the drug delivery of ciprofloxacin and investigation of antibacterial activity

Abstract: Today, metal-organic frameworks (MOFs) for the release of drugs have been studied extensively. In this research, we have investigated the novel magnetic framework including Fe 3 O 4 @PAA@ZIF-8 for the delivery of ciprofloxacin (CIP) antibiotic. Moreover, the antibacterial activity of Fe 3 O 4 @PAA@ZIF-8 and Fe 3 O 4 @PAA@ZIF-8@CIP screened against Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) bacteria. The structure of the nano carrier, as well as the encapsulation of the drug in the framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(29 citation statements)
references
References 34 publications
1
27
1
Order By: Relevance
“…Studies have shown that under the condition of pH ¼ 7.4, the drug releases about 74% aer 24 hours and then remains stable, and under the condition of pH ¼ 5, the drug release percentage aer 3 hours is about 64%, which is because of the degradation of the metal-organic framework in acidic medium leads to an accelerated release rate of CIP. 72 In terms of small molecules delivery, due to the poor physiological stability, non-specic targeting, and low cell membrane permeability of small molecules, a higher dose is generally required to achieve the desired therapeutic effect. However, higher dosages will increase drug tolerance and produce adverse side effects.…”
Section: Zif-8@mesoporous Nanoparticle Compositesmentioning
confidence: 99%
“…Studies have shown that under the condition of pH ¼ 7.4, the drug releases about 74% aer 24 hours and then remains stable, and under the condition of pH ¼ 5, the drug release percentage aer 3 hours is about 64%, which is because of the degradation of the metal-organic framework in acidic medium leads to an accelerated release rate of CIP. 72 In terms of small molecules delivery, due to the poor physiological stability, non-specic targeting, and low cell membrane permeability of small molecules, a higher dose is generally required to achieve the desired therapeutic effect. However, higher dosages will increase drug tolerance and produce adverse side effects.…”
Section: Zif-8@mesoporous Nanoparticle Compositesmentioning
confidence: 99%
“…[1,2,3] Most of the drawbacks can be decreased by effective and appropriative drug delivery systems (DDSs). [4,5] Nanoparticles (NPs) exhibit remarkable attributes such as the ability to protect drug from environmental factors, increasing drug stability in the bloodstream, transmission of low-soluble drugs, increasing fusion into target tissues and cells, capability to cross the blood-brain-barrier, increasing bioavailability in oral medicines, decreasing drug toxicity, prolonging circulation times, and reducing dose required for patients. [6,7] For these reasons, interests in targeted drug delivery system based on nanoparticles have extensively grown in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Although different drugs are versatile tools for the cure of intense sicknesses including cancer, Parkinson and cardiovascular diseases, they illustrate considerable disadvantages such as poor solubility and nonselective biodistribution, leading to toxicity damages to healthy tissues [1,2,3] . Most of the drawbacks can be decreased by effective and appropriative drug delivery systems (DDSs) [4,5] …”
Section: Introductionmentioning
confidence: 99%
“…Metal-organic frameworks (MOFs) are the practical and novel class of reticular chemicals with periodic network structure. MOFs have direct and indirect extensive applications in many fields including photocatalysts [1], CO2 capture [2], battery materials [3], supercapacitors [4], chemo-thermal therapy [5], separation agents [6,7], biosensors [8], and antibacterial agents [9]. Due to using various organic linker and secondary building units (SBUs), a wide range of these compounds has been synthesized for specific purposes [10⎼13].…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%